Efektifitas pemberian sari kedelai dan formula kedelai terhadap gula darah penderita diabetes mellitus tipe 2 - Wagustina, Silvia (JURNAL RISET GIZI, 2021)
Background : Diabetes mellitus is caused by a lack of insulin production in the body or insulin resistance. Soybeans can be used as a functional food to lower blood sugar levels because they have a low glycemic index value, sufficient fiber content, so they can slow down the absorption of food in the body, containing the amino acid arginine which is able to maintain the balance of the insulin hormone. Soybean isoflavones in the form of Genistein and Daidzein are useful for repairing cells, metabolizing glucose and fat, and protecting pancreatic cells.Methods : This type of research is a quasy experiment with a pre-post design with two treatment groups. The study was conducted from August to October 2020. The data collected were blood sugar levels, energy and carbohydrate intake, glycemic index, obesity status, physical activity and genetics. The research stages were: manufacture of soybean juice functional foods and soy formula. Functional food in the treatment group was given for 14 days. Data analysis used t-test dependent and independent statistical tests with a confidence degree of 95% (α 0.05) and continued with multiple linear regression analysis.Result : There is an effect of giving soy formula and soybean juice on blood sugar levels of people with Type 2 diabetes. The mean reduction in blood sugar levels in the group given soy formula was 26.30 mg/dl, while the group given soybean juice was 17.96 mg/dl.Conclution : Soybean formula can reduce blood sugar levels by 8.34 mg / dl greater than soybean juice. Physical activity carried out regularly has a role in reducing blood sugar levels by 33,828 mg / dl. Soybean juice and soy formulas can be used as alternatives to lower blood sugar levels in people with type 2 diabetes.